Analisis Pengaruh Metode Penyuluhan (Ceramah) Damapemberian Edukasi Minum Obat Pada Penderita Tb Paru - Mimi Dehmi; Andi Yusuf; Asrijun Juhanto (Jurnal Ilmiah Kesehatan Sandi Husada, 2021)
Introduction: tuberculosis is the second leading cause of death from infectious diseases in the world. Aim: determine the effect of health promotion methods in providing education on taking medication in patients with pulmonary TB. Methods: experimental research with posttest only control design Method Using a quasiexperimental Quasi Experiment Method The sample in this study was 27 people in each group so that the number of respondents was 54 people. Results: showed no significant difference between the attitudes of the experimental group and the control group The behavior of patients with pulmonary TB in the experimental group Mean Rank 43 11 and the control group Mean Rank 38 85 the difference in the value of delta 7 26 p-value 0 382 0 05 means that there is no significant difference between the behavior of the experimental group and the control group. Conclusion: that there is a significant effect between the implementation of health promotion counseling on the knowledge of pulmonary TB patients and there is no significant effect between the implementation of health promotion counseling on the attitudes and behavior of pulmonary TB patients.